Pelayanan Khusus Bagi Narapidana Perempuan Terhadap Pemenuhan Hak Kesehatan Reproduksi Di Lapas Kelas IIB Cilacap - Inggar Rinukti (Universitas Widya Gama Malang, 2021)
Women are special creatures created by God as ihsan who deserve to be loved and respected. Women were created by Allah SWT with the privilege of obtaining beauty and sophistication from the reproductive system. That the reproductive system is used as a tool to create offspring or new generations for mankind. On this basis, women are entitled to reproductive health services including female prisoners. Correctional institutions in Indonesia adhere to the correctional system, which is that the conceptual and historical system is very different from the prison system. The prison system is motivated by the concept of fostering and guiding it is very different from the prison system which is motivated by the concept of retaliation. Reflection on the concept of developing WBP (Correctional Assistance Residents) is based on the